Content and Language Integrated Learning (CLIL) in Indonesian Context: an Overview - Khoiriyah, Khoiriyah (FKIP Universitas Lampung, 2021)
Content and Language Integrated Learning (CLIL) in Indonesian Context: an Overview. Objectives: this study aims to give an overview of the implementation of CLIL in the Indonesian context from recent empirical studies. Methods: a systematic literature review was employed, including searching the literature, identifying the study, coding the study, conducting a quality appraisal, and doing thematic analysis. Findings: (1) CLIL is implemented as a framework for teaching material developments, (2) CLIL has been researched to seek the effect of implementation of CLIL on content comprehension, language skills and attitude, and (3) pedagogical suggestions were highlighted including improving teachers’ competence, initiating cooperation among content and language teachers and boosting students’ motivation. Conclusion: CLIL research in Indonesian EFL setting has been growing significantly in recent years. Some reported that CLIL approach is also collaborated with other approaches such as bilingual education, project-based learning, task-based learning and genre-based learning. Keywords: CLIL, Indonesia, systematic literature review, teaching approach.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202110